2017
DOI: 10.7717/peerj.3717
|View full text |Cite
|
Sign up to set email alerts
|

The microbial biosphere of the coral Acropora cervicornis in Northeastern Puerto Rico

Abstract: BackgroundCoral reefs are the most biodiverse ecosystems in the marine realm, and they not only contribute a plethora of ecosystem services to other marine organisms, but they also are beneficial to humankind via, for instance, their role as nurseries for commercially important fish species. Corals are considered holobionts (host + symbionts) since they are composed not only of coral polyps, but also algae, other microbial eukaryotes and prokaryotes. In recent years, Caribbean reef corals, including the once-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…The observed dominance of members of Proteobacteria, Bacteroidetes and Cyanobacteria phyla was expected considering findings from the global oceans (Sunagawa et al, 2015;Zinger et al, 2011) as well as previous studies of coral reefs and coastal associated niches (Curren & Leong, 2019;Feng et al, 2009;Godoy-Vitorino et al, 2017;Wegley et al, 2007). As expected, different classes of Proteobacteria phylum dominated water and sediment samples (Feng et al, 2009;Zinger et al, 2011): members of Gammaproteobacteria class were the most abundant in water samples whereas in the sediment samples Deltaproteobacteria were predominant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observed dominance of members of Proteobacteria, Bacteroidetes and Cyanobacteria phyla was expected considering findings from the global oceans (Sunagawa et al, 2015;Zinger et al, 2011) as well as previous studies of coral reefs and coastal associated niches (Curren & Leong, 2019;Feng et al, 2009;Godoy-Vitorino et al, 2017;Wegley et al, 2007). As expected, different classes of Proteobacteria phylum dominated water and sediment samples (Feng et al, 2009;Zinger et al, 2011): members of Gammaproteobacteria class were the most abundant in water samples whereas in the sediment samples Deltaproteobacteria were predominant.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, shifts in population composition of coral-associated microorganisms often correlate with the onset of diseases and coral-bleaching (Krediet et al, 2013), suggesting a likely role of microbes in coral health and, therefore, the stability of reef ecosystems. Besides health, microbes are also known to be critical for coral nutrition (Rosenberg et al, 2007) homeostasis and protection against diseases (Godoy-Vitorino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that differences between Heliconius species were restricted to rare OTUs can be rather important since rare taxa have been shown to be important in other biological systems. Distinct studies in soils ( Hausmann et al, 2016 ), human skin, human gut and the coral holobiont ( Shade et al, 2014 ; Godoy-Vitorino et al, 2017 ) have suggested that phylotypes with very low abundance (rare taxa) are likely to be functionally relevant.…”
Section: Discussionmentioning
confidence: 99%
“…gibbosa were from Streptococcus. All three of these bacterial genera have been observed in coral microbiomes (Beleneva et al, 2005;de Castro et al, 2010;Godoy-Vitorino et al, 2017).…”
Section: Influence Of Bleachingmentioning
confidence: 99%